Food and drug law : - Hutt, Peter Barton (Foundation Press Thomson/West, 2007)
Food and drug law deals with governmental attempts to protect public health and individual welfare in the development and marketing of essential commodities. The materials included in this Third Edition, the organization used, and the issues dealt with reflect this focus. The organization and bibliographic assistance should help frame the pertinent questions and identify many of the relevant sources. The FDA's continuing efforts to come to grips with its regulatory responsibilities comprise a mini-history of American administrative law. Since the 1960's, regulation of food, drugs, and related products has presented some of the most challenging illustrations of the tense interplay between law and science. Because of the growing complexity of its responsibilities and the potential clash between public objectives, the FDA has been forced to experiment with a wide variety of innovative administrative procedures for deciding controversial law-science issues. The story of federal efforts to regulate the marketing of foods and drugs is fascinating as history in itself.